Prevalence of Colistin-Resistant Escherichia coli from Poultry in South Asian Developing Countries - Prabin Dawadi; Shrijana Bista; Sayara Bista (Veterinary Medicine International)
Background. Antimicrobial resistance has become a huge problem in animal and public health worldwide. Inadvertent use of antibiotics in poultry has led to the emergence of resistance against many antibiotics, even to last resort of drugs like colistin. Aim. This study aimed to provide uniform quantitative estimate on the percentage prevalence of E. coli as well as to analyze their colistin resistance in poultry in South Asian developing countries. Methods. Two electronic databases, PubMed and Research4Life, were used to search studies as per the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines. The pooled data on the prevalence of E. coli and colistin resistance were analyzed. Results. In the meta-analysis of 9 studies in South Asian region (Nepal, Bangladesh, Pakistan, and India), the pooled prevalence of E. coli was 73% (95% CI, 0.549–0.916). The pooled prevalence of colistin resistance against E. coli from poultry was found to be 28% (95% CI, 0.158–0.438). Conclusion. There is high prevalence of E. coli and their resistance rate against colistin in poultry. Therefore, antimicrobials in raising livestock should be supervised.